Pollen viability and floral biology of Mandacaru (Cereus jamacaru (DC) (Cactaceae)) (Research, Society and Development, 2020)
Pollen fertility is indicated by viability, which influences the reproductive success of plants. Mandacaru is a native tree species with natural distribution in the Caatinga. The objective was to verify the pollen viability, pollen per ovule ratio and the morphological identification of the mandacaru flower (Cereus jamacaru). Ten flower buds were used and one hundred anthers of these buds, which and stained with Alexander dye on checkered glass slide and viable and non-viable pollens were accounted amount of ovule per flower bud was counted the pollen/ovule ratio. Mandacaru presented viability of 99.41% the pollen, with an average of 314,686 pollens on each flower. There were 356 pollens for each ovule, this indicates the species reproductive system for facultative autogamous and facultative xenogamics. The flower is hermaphrodite, with gynoecium measuring an average of 160.9 mm, an average of 883 ovules per flower, the androecium averaging 577 anthers per flower, 545 pollen per anther. Mandacaru has high pollen viability, with large size hermaphrodite flower, with high number of anthers and pollen contained in these anthers.